Comparative Analysis of Biomechanical Variables in Marker-based and Markerless Motion Capture Systems - D. I. Guseinov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
Motion capture systems are a key tool for performing quantitative analysis and evaluation of complex in movements sports. The prospect of the development and practical application of markerless motion capture tecnology in applied biomechanics increases research interest regarding the features of using such systems, as well as evaluat ing their accuracy and reliability in comparison with marker-based motion capture systems, which are the gold standard nowadays. Markerless motion capture systems have incomparable advantages over marker-based ones.In particular, significantly reduced time costs for the registration and data processing procedures, since registration is represented by filming a video from different angles, and processing is accompanied by the use of software algorithms for tracking the silhouette of an athlete using a presetted computer avatar. However, there is still no clear answer regarding the accuracy and reliability of the data recorded using markerless motion capture systems in relation to specific sports movements. Thus, the purpose of the presented work is to assess the statistical relationship of the data based on the correlation analysis of biomechanical variables on the example of a golf swing recorded using the Qualisys motion capture system and Simi Reality Motion markerless motion capture system.